Cardiovascular Autonomic Neuropathy. Issue 2 (1st April 2016) - Mccarty, Niamh; Silverman, Barry
Abstract : Cardiovascular autonomic neuropathy often goes unrecognized. We present a case of a 22-year-old man with multiple manifestations of this disease, including weakness, dizziness, fatigue, tachycardia, abnormal QTc, and orthostasis, which occurred 2 years after his type 1 diabetes diagnosis. He exhibited parasympathetic denervation with resting tachycardia and exercise intolerance but also had evidence of orthostatic hypotension, which suggests sympathetic denervation. He did not have complete cardiovascular autonomic reflex testing, which would have been helpful, but improved with aggressive diabetes treatment and the increase of beta-blockade. It is important to identify these patients to understand their signs and symptoms and consider appropriate therapies.